Rationale for the Use of CAD/CAM Technology in Implant Prosthodontics - Jaafar Abduo; Karl Lyons (International Journal of Dentistry)
Despite the predictable longevity of implant prosthesis, there is an ongoing interest to continue to improve implant prosthodontic treatment and outcomes. One of the developments is the application of computer-aided design and computer-aided manufacturing (CAD/CAM) to produce implant abutments and frameworks from metal or ceramic materials. The aim of this narrative review is to critically evaluate the rationale of CAD/CAM utilization for implant prosthodontics. To date, CAD/CAM allows simplified production of precise and durable implant components. The precision of fit has been proven in several laboratory experiments and has been attributed to the design of implants. Milling also facilitates component fabrication from durable and aesthetic materials. With further development, it is expected that the CAD/CAM protocol will be further simplified. Although compelling clinical evidence supporting the superiority of CAD/CAM implant restorations is still lacking, it is envisioned that CAD/CAM may become the main stream for implant component fabrication.